The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s11912-004-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemotherapy and external beam radiotherapy for transitional cell carcinoma of the bladder

Abstract: A growing body of evidence supports the treatment of invasive transitional cell carcinoma of the bladder with transurethral resection, chemotherapy, and external beam radiotherapy. Randomized trials have demonstrated the superiority of chemotherapy plus radiotherapy to radiotherapy alone. Several series with 10 years of follow-up demonstrate that the success of this approach can be maintained. Preservation of the urothelium, however, results in continued risk of de novo bladder cancer development in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…It has been pointed out in the literature that randomized trials have demonstrated the superiority of chemotherapy plus radiotherapy to radiotherapy alone [57,58]. These trials have been performed with chemotoxic agents being different from the radiotoxic agents.…”
Section: Combining Radiotoxicity With Chemotoxicity?mentioning
confidence: 99%
“…It has been pointed out in the literature that randomized trials have demonstrated the superiority of chemotherapy plus radiotherapy to radiotherapy alone [57,58]. These trials have been performed with chemotoxic agents being different from the radiotoxic agents.…”
Section: Combining Radiotoxicity With Chemotoxicity?mentioning
confidence: 99%